Real-world retrospective analysis of patient characteristics, healthcare resource utilization, costs, and treatment patterns among unvaccinated adults with COVID-19 diagnosed in outpatient settings in the United States. (31st December 2022) - Scott, Amie; Chambers, Richard; Reimbaeva, Maya; Atwell, Jessica; Baillon-Plot, Nathalie; Draica, Florin; Tarallo, Miriam
Abstract: Aims: This retrospective analysis of the Optum Clinformatics Data Mart database evaluated US patient characteristics, healthcare resource utilization (HCRU), costs, and treatment patterns among unvaccinated adults with outpatient-diagnosed COVID-19 to quantify US economic burden. Materials and methods: The index event was the earliest outpatient diagnosis of confirmed COVID-19 from May 1 to December 10, 2020. Patients had 12 months' continuous enrollment before and were followed for ≥60 days after index date until insurance dis-enrollment or study end. Results: 236, 589 patients had outpatient-diagnosed COVID-19 (7, 692 with and 228, 897 without subsequent COVID-19-related inpatient admission >48 h post-diagnosis). The median age was 51 years (≥65 years, 30.0%); 72.4% had ≥1 risk factor. Patients with versus without subsequent inpatient admission were more often male, older, Black/Hispanic, and had comorbidities/risk factors. With a median follow-up of 162 days, patients had a median of 1 COVID-19-related outpatient visit (with inpatient admission, 5 outpatient visits). Those with inpatient admission had a median of 1 COVID-19-related inpatient visit (median length of stay [LOS], 6 days), 33.3% were admitted to intensive care (median LOS, 8 days), 8.4%, 7.1%, and 13.3% received invasive mechanical ventilation, noninvasive mechanical ventilation, and supplemental oxygen, respectively; 13.5% experienced readmission. Inpatient mortality was 6.0% (0.3% for nonhospitalized patients). Antithrombotic therapy, antibiotics, corticosteroids, and remdesivir use increased among patients with inpatient admission versus without. Median total COVID-19-related non-zero medical costs were 208 for patients without inpatient admission (with inpatient admission, 39, 187). Limitations: Results reflect the circulating SARS-CoV-2 and treatment landscape during the study period. Requirements for continuous enrollment could have biased the population. Cost measurements may have included allowed (typically higher) and charge amounts. Conclusions: Given the numbers of the US population who are still not fully vaccinated and the evolving epidemiology of the pandemic, this study provides relevant insights on real-world treatment patterns, HCRU, and the cost burden of outpatient-diagnosed COVID-19.